DIVIDEND POLICY AND SHAREHOLDERS’ WEALTH OF LISTED IT COMPANIES IN INDIA - N. Moses; M. Yugandharudu; P. Suchitra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the modern financial landscape, dividend policy remains a pivotal aspect of corporate financial management. It reflects a company’s approach to distributing profits to its shareholders and directly influences investor perceptions, market valuation, and long-term wealth creation. Dividend policy serves as both a financial decision and a strategic signal. It conveys management’s outlook on future earnings, liquidity, and confidence in sustaining growth. For shareholders, especially those seeking predictable returns, dividends offer a tangible reward and assurance of the firm’s financial health. However, the relationship between dividend policy and shareholder wealth has been a subject of debate, with theories like the Modigliani-Miller Hypothesis suggesting irrelevance, and others like the Bird-in-the-Hand and Signaling theories arguing for positive correlation. The Indian IT sector is unique due to its high free cash flows, asset-light models, and global clientele, enabling companies to maintain regular payouts even during uncertain times. Despite being growth-oriented, many Indian IT firms adopt a balanced dividend policy, aiming to reward shareholders while retaining enough earnings for reinvestment. Particularly in India’s dynamic Information Technology (IT) sector, listed firms like Infosys, TCS, Wipro, and HCL Technologies have emerged as strong players not only in service delivery but also in maintaining sound financial strategies, including stable and consistent dividend practices. The Information Technology (IT) sector in India has become a major contributor to GDP and stock market performance. This study seeks to explore the impact of dividend policy on shareholders’ wealth in the context of listed IT companies in India. By analyzing payout trends, stock market responses, and total shareholder returns, the research aims to provide insights into how dividend decisions contribute to the overall financial strategy and market standing of these firms.